Loop dynamics behind the affinity of DARPins towards ERK2: Molecular dynamics simulations (MDs) and elastic network model (ENM) - Gautam, Vertika; Chong, Wei Lim; Chin, Sek Peng; Zain, Sharifuddin Md; Abd Rahman, Noorsaadah; Vao-soongnern, Visit; Lee, Vannajan Sanghiran (Elsevier, 2019)
The binding affinity and dynamics profiles of non-phosphorylated extracellular regulated kinase 2 (ERK2), in complex with DARPins (designed ankyrin repeat proteins) as a phosphorylation inhibitor, has been investigated using molecular dynamics simulations (MDs) and elastic network model (ENM). The study investigates the effect of ERK2 loop dynamics on its specificity, upon binding with DARPins. From experiments, DARPin E40 has been found as a specific binder (E40/ERK2) with higher binding affinity while DARPin pE59 has lower binding affinity towards ERK2 (pE59/ERK2). Theoretical binding affinities along the 100 ns molecular dynamics simulations between DARPins and ERK2 were analyzed and found in good agreement with the experiments, where BFE (binding free energy) of E40/ERK was found to be much lower (more favorable) as compared to that of pE59/ERK2 with the contribution of activation loop and αG loops. Moreover, elastic network model (ENM) studies successfully delineate the dynamics of four loops of ERK2 (activation, αG, MAPK and L16) along the trajectories. Slow eigenvectors from global mode shapes and dynamic cross correlation indicate the responsible regions for the binding. The specificity of DARPins can be discriminated by the binding free energy of the activation and αG loop, which indicated the stronger interaction of these region in E40/ERK2. Robustness of the average properties (mean-square fluctuations, eigenvectors from global mode shapes, dynamic cross-correlations) controlled by the low frequency motions, which are reproduced in both MDs and ENM suggested that GNM based on a coarsegrained single-site-per-residue model can be used as a complimentary and fast analytical approach to investigate the structural dynamics.